Metal-organic-frameworks derived cobalt embedded in various carbon structures as bifunctional electrocatalysts for oxygen reduction and evolution reactions - Binling Chen (Nature Portfolio, 2017)
Abstract A series of nanocomposites of cobalt embedded in N-doped nanoporous carbons, carbon nanotubes or hollow carbon onions have been synthesized by a one-step carbonization of metal-organic-framework ZIF-67. The effect of the carbonization temperature on the structural evolution of the resulting nanocomposites has been investigated in detail. Among the as-synthesized materials, the cobalt/nanoporous N-doped carbon composites have demonstrated excellent electrocatalytic activities and durability towards oxygen reduction reaction in alkaline medium. Compared to the benchmark Pt/C catalyst, the optimized Co@C-800 (carbonized at 800 °C) exhibited high oxygen reduction reaction activity with an onset potential of 0.92 V, and a half-wave potential of 0.82 V. Moreover, the optimized Co@C-800 also showed enhanced electrocatalytic activity towards oxygen evolution reaction from water splitting, with a low onset potential of 1.43 V and a potential of 1.61 V at 10 mA cm−2 current density. This work offered a simple solution to develop metal-organic-framework-derived materials for highly efficient electrochemical applications.